DNA methylation and gene deletion analysisof brain metastases in melanoma patients identifies mutually exclusive molecular alterations - Marzese, Diego Matías (2014)
Background: The brain is a common target of metastases for melanoma patients. Little is known about the genetic and epigenetic alterations in melanoma brain metastases (MBMs). Unraveling these molecular alterations is a key step in understanding their aggressive nature and identifying novel therapeutic targets. Methods: Genome-wide DNA methylation analyses of MBMs (n = 15) and normal brain tissues (n = 91) and simultaneous multigene DNA methylation and gene deletion analyses of metastatic melanoma tissues (99 MBMs and 43 extracranial metastases) were performed. BRAF and NRAS mutations were evaluated in MBMs by targeted sequencing. Results: MBMs showed significant epigenetic heterogeneity. RARB, RASSF1, ESR1, APC, PTEN, and CDH13 genes were frequently hypermethylated. Deletions were frequently detected in the CDKN2A/B locus. Of MBMs, 46.1% and 28.8% had BRAF and NRAS missense mutations, respectively. Compared with lung and liver metastases, MBMs exhibited higher frequency of CDH13 hypermethylation and CDKN2A/B locus deletion. Mutual exclusivity between hypermethylated genes and CDKN2A/B locus deletion identified 2 clinically relevant molecular subtypes of MBMs. CDKN2A/B deletions were associated with multiple MBMs and frequently hypermethylated genes with shorter time to brain metastasis. Conclusions: Melanoma cells that colonize the brain harbor numerous genetically and epigenetically altered genes. This study presents an integrated genomic and epigenomic analysis that reveals MBM-specific molecular alterations and mutually exclusive molecular subtypes.